Strain regime induced by axial compression in slender reinforced concrete columns using different mathematical approaches. (March 2023) - Magalhães, Kaique Moreira Matos; de Macêdo Wahrhaftig, Alexandre; da Fonseca Brasil, Reyolando Manoel Lopes Rebello
Abstract: A mathematical investigation to determine the strain regime induced by normal compression force in concrete, including the portion due to material creep, was presented. The consideration of creep suggests the possibility of changing the constitutive law of the material since it introduces a temporal variation, hence the need to use different mathematical paths to evaluate the imposed strains. The analysis was conducted on a real reinforced concrete column, with variable geometry and high slenderness ratio, on which two different approaches were considered. In the first one, a concrete stress–strain curve, standardized by a technical norm, was used. In the second one, the integration of differential relations of displacements along the length of the structure was adopted. The analysis was performed by considering the structural system loaded by just its self-weight to the critical buckling load.